Relação dos biomarcadores pró-inflamatórios e neurotróficos no status cognitivo, percepção dolorosa e dano celular na fase subaguda pós-AVCi - Grignet, Rodrigo Juliano (2024)
Stroke is the second leading cause of death worldwide among chronic degenerative diseases, and survivors may experience somatosensory, cognitive and executive changes, as well as persistent spasticity and pain. Neuroinflammation resulting from the disease appears to be correlated with the formation of micronuclei in the nervous system, structures common in cancers, neurodegenerative diseases and other conditions related to aging, indicating genomic instability and cellular stress. On the other hand, biomolecules such as tumor necrosis factor alpha and brain-derived neurotrophic factor are related to the disease in its various phases. In addition, factors such as obesity, high blood pressure and polypharmacy use influence the patient's overall condition and functional recovery. The aim of this study was to relate ischemic stroke to genomic instability, biomarkers and neurocognitive aspects associated with pain, polypharmacy, blood pressure and body mass. The methodology included the collection of sociodemographic, anthropometric, hemodynamic and biological data. The final sample consisted of 56 individuals of both sexes, divided into two groups: one with 33 participants affected by the disease in the subacute phase with a mean interval of 43 days since the event, and who were not undergoing outpatient physiotherapy treatment at the time of collection; and a control group of 23 individuals in the same age group. The Mini-Mental State Examination and McGill pain questionnaires were applied and the modified Ashworth scale was used to assess spasticity. The collected blood was processed for detection of biomolecules by the ELISA method and counting of the frequency of micronuclei by means of smear and culture techniques. Quantitative variables were evaluated by the Shapiro-Wilk and homoscedasticity tests. Those that met the assumptions were compared by the t-test, while the others were compared between the groups by the nonparametric Mann-Whitney-U test, with a significance level of 0.05. Variance partitioning analysis was applied, based on partial redundancy analysis, to test the effect of each matrix of independent variables and the results were interpreted together. All analyses were performed using R Core Team software, 2021. The results showed statistically significant data in several dimensions evaluated between the sample groups, highlighting the group with the pathology. The presence of micronuclei in smear (p-value: 0.0003), micronucleus culture (p-value: 0.0133), high systolic blood pressure (p-value: 0.0047), diastolic blood pressure (p-value: 0.0149), spasticity (p-value: < 0.0001), cognitive impairment (p-value: 0.0005) and polypharmacy (p-value: < 0.0001) were observed. Variance partitioning revealed that the multifactorial nature of ischemic stroke significantly impacts the functional status of patients in 73%. A relationship was observed between genetic damage, cognitive repercussions and persistent pain, suggesting that ischemic stroke comprehensively compromises the functional and cognitive dimensions and quality of life of affected individuals. Although the data point to this association, further investigations are needed to determine whether other factors, in addition to genetic damage per se, associated with advanced age, contribute to the magnitude of this effect. This complexity makes the multifactorial issue even more challenging.